Informação para a ação: o uso da informação como suporte às reivindicações sindicais no âmbito da segurança e da saúde do trabalhador - Sheila Margareth Teixeira Adao (2008)
It searches to understand how information may stablish and direct the development of actions to protect health and safety undertaken by union leaders of the Departments of Health from Metalworkers Union of Belo Horizonte and Contagem, and the Bankworkers Union of Belo Horizonte and Region. The specific objectives of this dissertation are: to identify elements that make up the union contemporary discourse about the safety and health of the worker, which examine the importance given to information in that speech; to characterize the informational guidelines suggested by the International Labour Organization (ILO), the FUNDACENTRO and the National Institute of Health at Work (INST), identifying if in the referred unions, these guidelines become information policies; to understand what is the information role on trade unions action in defense of workers' health; and to verity if the unions surveyed have structured the information to subsidies their actions. It presents the main aspects of safety and health of the worker over the years and the performance of Brazilian trade union movement on the issue. It includes some thoughts on information as a support to social and trade union demands. This shape the institutions for promotion and dissemination of information to defend the worker safety and health (ILO, and FUNDACENTRO INST). It analyses the relationship between information, power and trade union actions. The study is based on an exploratory survey, having as sample nine social actors directly involved in the actions of workers in safety and health. By means of semi-structured interviews it features the role occupied by information on health and safety of workers in the unions policies studied.